Impact of Online Advertisement on Customer Satisfaction With the Mediating Effect of Brand Knowledge - Salameh, Anas A.; Ijaz, Mahrukh; Omar, Abdullah Bin; Zia ul Haq, Hafiz Muhammad (Frontiers in Psychology, 2022)
The purpose of this article is to explain how online advertising affects customer satisfaction through the mediation of brand knowledge. The sample size of this survey is based on 100 participants in the Multan region. This study collects data by conducting various unstructured interviews. In this study, we used a qualitative data acquisition technique. The results show that online advertising does not have a significant impact on customer satisfaction. However, when brand knowledge is included as a parameter, the correlation between online advertising and customer satisfaction increases. Online advertising is a new advertising tool used by most organizations. This manuscript helps practitioners choose better tools for online promotion and uses a variety of recognition techniques to improve their brand knowledge. It has been known through this study, that building customer confidence in product quality is a very effective approach in front of business owners, as brand reputation enhances customer satisfaction. This study is unique in that previous studies considered elements of brand knowledge as parameters and ignored to find a direct relationship between online advertising and customer satisfaction. This study highlights key points that will help emerging researchers critically analyze such aspects in future studies.